Pengaruh Volume Perdagangan, Laba Akuntansi, dan Profitabilitas Terhadap Return Saham Syariah Dimoderasi Pengungkapan ISR - Ani Murtaza; Alvita Tyas Dwi Aryani (Jurusan Akuntansi Syariah Fakultas Ekonomi dan Bisnis Islam UIN K.H. Abdurrahman Wahid Pekalongan, 2021)
The level of profit obtained by investors on a stock investment that they dois known through stock returns. A stock return can be influenced by severalfactors, one of which is the trading volume of its shares, the level of profit thatcan be known through the company's performance by analyzing accountingprofits and the level of Return on Equity (ROE). In addition to this, the disclosureof Islamic Social Reporting (ISR) activities can have an impact on the company inthe future. The populations in this research are companies listed in JakartaIslamic Index (JII) in period of 2016-2019. The sampling technique was carriedout using purposive sampling method and based on the criteria that had beencarried out, the number of samples obtained was 12 samples of companies.Testing the research hypothesis used multiple linear regression analysistechniques and Moderating Regression Analysis (MRA) with the help of SPSS 21software. The results of this study indicate that the variables (1) trading volumehas an effect and significant on sharia stock returns (2) accounting profit has noand no significant effect on sharia stock returns (3) Profitability proxied byReturn on Equity (ROE) has no and no significant effect on sharia stock returns(4) ISR disclosure is not able to moderate the effect of trading volume, accountingprofit and profitability on sharia stock returns.